2013
DOI: 10.1111/j.1540-5850.2013.12002.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Government Capital Spending in Indonesia: Impact of Intergovernmental Fiscal Transfers

Abstract: Indonesian policymakers intend to increase capital spending, especially on traditional infrastructure, at all levels of government in order to stimulate economic growth. Intergovernmental capital grants can have very significant impact on encouraging such spending at the subnational level. The main problems with capital transfers in the Indonesian context are that grant funding has stagnated at low levels and the proportion of funding allocated to infrastructure has declined considerably. Given current institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
(20 reference statements)
0
34
3
4
Order By: Relevance
“…The variables used are various local government revenues and other social-economic variables as control variables. This paper is mainly following Lewis [1] and Levaggi and Zanola [3] where they try to figure out the impact of intergovernmental fiscal transfer towards the regional government spending for capital spending in Indonesia and health in Italy respectively. This paper uses two models.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The variables used are various local government revenues and other social-economic variables as control variables. This paper is mainly following Lewis [1] and Levaggi and Zanola [3] where they try to figure out the impact of intergovernmental fiscal transfer towards the regional government spending for capital spending in Indonesia and health in Italy respectively. This paper uses two models.…”
Section: Methodsmentioning
confidence: 99%
“…Lewis [1] found that the largest marginal effect towards local expenditure spending in infrastructure was for a specific allocation fund. This is due to specific allocation fund which has more both income and the substitution effect whereas other type of grants only only income effects [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations